Hand Hygiene Compliance And Associated Factors Among Healthcare Workers With Critical Units In Jeddah (The Review of Diabetic Studies, 2025)
Background Hand hygiene is a major component of preventing healthcare-associated infections, particularly in acute care units where the patients are at increased risk of experiencing morbidity and death as a result of pathogen exposure. Although evidence-based (EB) recommendations have been put in place (ie, the WHO approach of Five Moments of Hand Hygiene) all over the world, including Saudi Arabia, adherence in healthcare workers (HCWs) is far from acceptable.Objective: This study was intended to evaluate hand hygiene compliance and determine factors that are related to healthcare workers working in critical units in Jeddah, Kingdom of Saudi Arabia.Method: The study utilized a quantitative cross sectional design. Purposive non-probability sampling was carried out to collect data among the HCWs in intensive care and emergency departments of the chosen hospitals in Jeddah between 2022 and 2023 and 2024 as of January and December. The questionnaires used in the collection of the data were a demographic sheet, and two questionnaires that have been validated (The Hand Hygiene Questionnaire and the WHO Hand Hygiene Perception Survey). The statistical analysis of data was carried out with the help of SPSS Version 28 software, where descriptive statistics and inferential statistics with Pearson correlation coefficient, independent t-test, analysis of variance, and linear regression were used.Results: The outcomes reported moderate adherence to hand hygiene practices among HCWs, and those results have shown significant associations between the rates of compliance and other variables, which were gender, profession, years of experience, and training attendance. Compliance behavior was correlated with knowledge and perception scores in a positive way.Conclusion: Decision: Understanding, perception, and institutional support are therefore key modifiable factors that should be given focused interventions that will help to increase hand hygiene compliance in the critical care unit.